Вісник Харківського національного університету імені В. Н. Каразіна. – 2003. - № 597. Cерія Медицина. – Вип. 6 - Харківський національний університет імені В.Н. Каразіна (Харківський національний університет ім. В.Н. Каразіна, 2003)
Journal contains articles about topical issues of modern experimental and clinical medicine
The Journal of V. N. Karazin Kharkiv National University. – 2003. - № 597. Series Medicine. – Issue 6
Keywords: Health Organization; Fundamental Research; Clinical Research; Reviews; Clinical Practice; Lectures; Medical Law; Ecology and Health; Philosophy of Medicine